PENGARUH PENERAPAN MEDIA AUGMENTED REALITY MENGGUNAKAN APLIKASI ARGEO LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IX SMPN 7 Mataran Tahun Ajaran 2024/2025 - Husnul Hotimah; Arjudin; Dwi Novitasari; Baidowi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of applying augmented reality media using the ARGEO Learning application on the mathematics learning outcomes of class IX students of SMP Negeri 7 Mataram in the 2024/2025 academic year. This research is an experimental study. The sample of this study was class IX B as the experimental class and IX D as the control class selected using the Cluster Random Sampling technique. The data collection technique in this study used a mathematics learning outcome test. The experimental class was given treatment by applying augmented reality media using the ARGEO Learning application. While the control class used manipulative object props as learning media. The data analysis used in this study was the t-test (independent sample t-test) polled variance. The results showed that the average value of the experimental class was higher than the average value of the control class where ≥ , then was accepted which means there was a difference in the average learning outcomes between students in the experimental class and students in the control class. From these differences, it can be concluded that there is an influence of the application of augmented reality media using the ARGEO Learning application on the mathematics learning outcomes of class IX students of SMPN 7 Mataram in the 2024/2025 academic year.